Adolescent Psychological Impact On Mental Health During Pregnancy - Rr. Catur Leny Wulandari; Yunita Setiya Aryani; Arum Meiranny (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Pregnancy in adolescents can cause serious conditions such as physical and psychological conditions. Pregnancy among adolescents in low, middle, and high income countries is a problem that occurs globally. According to Who data (2012). There are around 16 million adolescents aged 15-19 giving birth each year. Meanwhile, in low income countries there are around 14% of pregnancies out of wedlock. Pregnancy is associated with significant risk to women’s mental health, one of which is the psychological condition of the expectant mother. The minimum age for a women to get married should be 21-22 years because she is considered physically and mentally capable. Adolescent who are pregnant less than the productive age of years will have an impact on their mental conditions such as anxiety, stress and depression. This study aims to find out more about the psychological impact on teenage pregnancy with existing studies by reviewing several research articles. The research design used a literature review with sources from computerized systematic search studies (Google Scholar and Pubmed) with the last 10 years recorder from 2014-2023. There were 60 articles obtained and after conducting a proper review of the title, there were 23 with 19 national articles and 4 international articles. The criteria for finding the key to searching the literature review are “mental health” and “adolescent pregnancy”